PENERAPAN ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN USAHA INDUSTRI KERAJINAN ROTAN (Studi pada Desa Trangsan Kecamatan Gatak Kabupaten Sukoharjo) - Silfia Oknita Puspitasari; Wikan Budi Utami; Suprihati Suprihati (ITB AAS INDONESIA, 2022)
This study aims to determine the application of SWOT Analysis as a business development strategy for the rattan handicraft industry in Trangsan Village, Gatak District, Sukoharjo Regency. This research uses qualitative research methods with data collection techniques in the form of interview, questionnaires, observations and documentations. The data analysis technique used is the SWOT Analysis technique. The results of this study indicate that the rattan handicraft industry is located in quadrant I, namely growth. Where this quadrant is a very profitable situation for the company because strengths and opportunities can be utilized at the same time and are able to overcome the weaknesses and threats that exist within the company.